(untitled) (Boletin Médico de Postgrado, 2024)
Ankle fractures are one of the most common bone injuries in the trauma emergency department, representing a high percentage of lower limb fractures. The aim of this research work was to determine the clinical-surgical management of patients with Weber B ankle fractures who attended the Traumatology and Orthopedics Service at the Dr. Antonio María Pineda Central University Hospital during the period January 2022 to January 2023. Two hundred patients with a mean age of 39.56 ± 13.42 years were included. Pain and functional limitation was present in all cases. Other symptoms included edema (97%), crampy bony ankle deformity (43%) and bony exposure (6%). The left side was the most affected (53%). Eighty percent of the patients received surgical treatment. The patient’s evolution was favorable in 70% of the cases; 72% received post-surgical rehabilitation. However, treatment failure was observed in 10% of the patients, many of them belonging to the conservative management group.